THE ANALYSIS OF THE BEER SECTOR IN ROMANIA - OANA DOBRE-BARON (Annals of the University of Petrosani: Economics, 2012)
This study aims to analyse a sector of the Romanian economy which is currently among the most sustainable. It is about production and marketing of beer, a product with a long and rich history around the world but also in Romania. The analysis covers a period of seven years and takes into account the dynamic evolution of those market-specific indicators such as: production, consumption, imports, exports, workforce involved, the contribution to the state budget, etc.